Sport-Related Affective Benefits for Teenagers Are Getting Greater as They Approach Adulthood: A Large-Scale French Investigation - Carton, Annie; Barbry, Alexis; Coquart, Jérémy; Ovigneur, Hervé; Amoura, Camille; Orosz, Gabor (Frontiers in Psychology, 2021)
The present investigation examined how sports club membership is related to adolescents’ daily negative and positive affects as they age. Robust prior results demonstrated that sports club membership is positively related to positive affect and negatively related to negative affect. However, surprisingly, no prior studies examined whether these benefits are consistently present throughout the teenage years or there are certain critical periods when teenagers can affectively profit more from being members of a sports club. The present cross-sectional investigation examined these questions on a comprehensive sample of French adolescents (N=17,337, female=7,604, aged between 10 and 18, Mage=12.45years, SDage=1.94years). Besides the expected affective benefits of a sports club membership, there was no interaction between age and negative affect. However, late adolescents reported greater daily positive affective benefits of sports club membership than early adolescents. These results suggest that late adolescents can use the extra affective benefits of sports club membership to gain advantages for the first steps of their adult life, such as coping with career start or transition to higher education. These results can provide guidelines for future studies to prioritize late adolescents with heightened positive sport-related affective benefits. It can also be useful information to promote sport among late adolescents.